Massive Embolism: Knife versus PCI - Tohme, Scarlett; Newman, Joshua S.; Gasparis, Christopher; Manetta, Frank (International Journal of Angiology, 2022)
Pulmonary embolism is the third most common cardiovascular syndrome with an estimated up to 25% of patients presenting with sudden death. For those who survive, a mainstay of management for patients with hemodynamic stability is anticoagulation; however, recommendations and options are rapidly changing for patients with submassive or massive pulmonary embolism with hemodynamic instability. Catheter-based and surgical approaches offer efficacious management options for unstable patients or patients with contraindications to anticoagulation; however, both approaches have inherent benefits and risk. This article seeks to offer a brief review on the recommendations and options for management of pulmonary embolism from both surgical and catheter-based perspectives.
Keywords: pulmonary embolism; catheter-directed thrombolysis; catheter-based embolectomy; surgical pulmonary embolectomy; extracorporeal membrane oxygenation; ECMO